2015
DOI: 10.1016/j.bbapap.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic roles of βLys87 in tryptophan synthase: 15N solid state NMR studies

Abstract: The proposed mechanism for tryptophan synthase shows βLys87 playing multiple catalytic roles: it bonds to the PLP cofactor, activates C4′ for nucleophilic attack via a protonated Schiff base nitrogen, and abstracts and returns protons to PLP-bound substrates (i.e. acid-base catalysis). ε-15N-lysine TS was prepared to access the protonation state of βLys87 using 15N solid-state nuclear magnetic resonance (SSNMR) spectroscopy for three quasi-stable intermediates along the reaction pathway. These experiments esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…We previously reported that the βLys87 amino group is neutral and resonates at 24.2 ppm in the TS aminoacrylate intermediate, and the addition of 2AP to form the quinonoid correlates with the loss of this resonance. 37 These data suggest that upon moving from the aminoacrylate to the 2AP quinonoid form, the βLys87 side chain switches from neutral to positively charged, consistent with the proposed mechanism in which βLys87 plays alternating acid and base roles. 37 To directly observe the βLys87 resonance, we take advantage of the fact that it is the only lysine residue within the active site and the only lysine with close spatial proximity to the phosphate group of PLP; the crystal structure shows that βLys87 and the cofactor phosphate are hydrogen bonded with a distance of 3.7 Å between the PLP phosphorus atom and the side chain ε-nitrogen (PDB ID: 4HPJ).…”
Section: Results and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We previously reported that the βLys87 amino group is neutral and resonates at 24.2 ppm in the TS aminoacrylate intermediate, and the addition of 2AP to form the quinonoid correlates with the loss of this resonance. 37 These data suggest that upon moving from the aminoacrylate to the 2AP quinonoid form, the βLys87 side chain switches from neutral to positively charged, consistent with the proposed mechanism in which βLys87 plays alternating acid and base roles. 37 To directly observe the βLys87 resonance, we take advantage of the fact that it is the only lysine residue within the active site and the only lysine with close spatial proximity to the phosphate group of PLP; the crystal structure shows that βLys87 and the cofactor phosphate are hydrogen bonded with a distance of 3.7 Å between the PLP phosphorus atom and the side chain ε-nitrogen (PDB ID: 4HPJ).…”
Section: Results and Discussionsupporting
confidence: 73%
“…37 These data suggest that upon moving from the aminoacrylate to the 2AP quinonoid form, the βLys87 side chain switches from neutral to positively charged, consistent with the proposed mechanism in which βLys87 plays alternating acid and base roles. 37 To directly observe the βLys87 resonance, we take advantage of the fact that it is the only lysine residue within the active site and the only lysine with close spatial proximity to the phosphate group of PLP; the crystal structure shows that βLys87 and the cofactor phosphate are hydrogen bonded with a distance of 3.7 Å between the PLP phosphorus atom and the side chain ε-nitrogen (PDB ID: 4HPJ). The other 26 lysines in the TS αβ-dimer are located on the exterior of the protein, and none is closer than 11.1 Å to the PLP phosphorus or 9.5 Å to the F9 phosphorus (the only other phosphorus atom present in the complex).…”
Section: Results and Discussionsupporting
confidence: 73%
“…Recent ssNMR studies provided chemical shifts for selected atoms of the E(Ain) intermediate and have established that the SB linkage of the Lys87 ε-imine nitrogen is protonated while the pyridine nitrogen (PN) is deprotonated for this species. 34 However, for the E(A-A), E(Q) indoline , and E(Q) 2AP , previously published 32 and additional chemical shift data 35 (unpublished data; manuscript in preparation) seem to support the idea that the proton shifts from the SB nitrogen to the phenolic oxygen (PO), at least as the majority species. However, the predominant protonated PO structures appear to participate in proton exchange both with the carboxylate oxygen (CO) and, to a lesser extent, the SB nitrogen in the E(Q) indoline and E(Q) 2AP forms (Scheme 1; Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, nuclear spin interactions, including the chemical shift, dipolar, and quadrupolar tensors, are sensitive probes of dynamics over many decades of motional timescales, from picoseconds to seconds, making NMR a unique technique for probing motions over the entire range of functionally relevant time scales, often in a single sample as demonstrated for GB1 (Lewandowski et al, 2015) and thioredoxin (Yang et al, 2009). MAS NMR is particularly well suited for probing protein dynamics in large biological assemblies and has shed light on a number of intriguing biological questions, such as gating of membrane proteins (Hu et al, 2010; Wang & Ladizhansky, 2014; Weingarth et al, 2014; Wylie et al, 2014), mechanisms of enzyme catalysis (Caulkins et al, 2015; Rozovsky & McDermott, 2001; Schanda et al, 2014; Ullrich & Glaubitz, 2013), and the regulation of protein-protein interactions in supramolecular assemblies (Hoop et al, 2014; Opella et al, 2008; Yan et al, 2015b). Unlike in solution NMR, the anisotropic tensorial spin interactions are recorded in MAS NMR rather than the motionally averaged residual interactions.…”
Section: Current Methodology For Structural and Dynamics Analysis mentioning
confidence: 99%